AB0050 Association of il12b gene polymorphisms with ankylosing spondylitis. (23rd January 2014) - Ivanova, M.; Manolova, I.; Miteva, L.; Stoilov, N.; Stoilov, R.; Rashkov, R.; Stanilova, S.
Abstract : Background: IL12B encodes the IL-12p40 subunit of both the IL-12 and IL-23 cytokines, which play critical and unique roles in bridging the innate and adaptive immune systems. Whereas IL-12 induces development of Th1 cells, which produce IFN-gamma, IL-23 is involved in Th-17 cells that appear to play a role in the pathogenesis of ankylosing spondylitis (AS). Although the precise etiology of AS is unclear, high prevalence of HLA-B27 predisposition and predominantly involved pro-inflammatory cytokines suggest a substantial association with an immunogenetic basis and support the hypothesis that IL12B gene polymorphisms could affect the development of AS. Objectives: In this regard, the aimof this study was to determine whether genetic polymorphisms of the IL-12B gene are associated with AS in Bulgarian populationby genotyping for A/C SNP in the 3′-UTR of the IL-12B (rs3212227) and IL12Bpro (rs17860508), a complex polymorphism in promoter region of the IL12B, resulting from 4 bp microinsertion combined with AA/GC transition. Methods: A total of 58 patients with AS and 132 matched healthy individuals were enrolled it the study. Genotyping for the rs3212227was performed by restriction fragment length polymorphisms-PCR assay and for the rs17860508 by allele specific-PCR. Results: There were no significant differences in the genotype and allele frequencies of rs3212227 and rs17860508 polymorphism of the I L12B between AS patients and controls. However, in logistic regression analysis the presence of 3′-UTR allele C in the genotype (CT + CC vs. TT) and IL12Bpro allele 2 in the genotype (1.2+2.2 vs. 1.1) were associated with an increasing risk of developing AS (OR=1.454 and OR-2.04, respectively). Also, AS patients carrying 3′-UTR CC genotype had earlier age at diseases onset (20.6±5.97 years) than those carrying allele A in the genotype (AA+AC; 27.8±7.93 years; p=0.054). In addition, the presence of IL12Bpro allele 2 in the genotype (1.2+2.2 vs. 1.1) is associated with increased risk of peripheral joints involvement (OR=2.625) and the carriage of IL12Bpro genotype 2.2 is associated with 2-fold increased risk of having higher functional disability (BASFI>4; OR=2.286). Conclusions: In conclusion, our data support the hypothesis that genetic variations in IL12B gene affecting inducible production of IL-12p40, may contribute to development of AS in the Bulgarian population. Disclosure of Interest: None Declared